Vertically Integrated System with Microfabricated 3D Sensors and CO2 Microchannel Cooling - Da Via, Cinzia; Petagna, Paolo; Romagnoli, Giulia; Hellenschmidt, Desiree; Munoz-Sanchez, Francisca; Dann, Nicholas (Frontiers in Physics, 2021)
The growing demand for miniaturized radiation-tolerant detection systems with fast responses and high-power budgets has increased the necessity for smart and efficient cooling solutions. Several groups have been successfully implementing silicon microfabrication to process superficial microchannels to circulate coolants, in particular, in high-energy physics experiments, where the combination of low material budget to reduce noise generated by multiple scattering events and high radiation fluences is required. In this study, we report tests performed on an 885-µm–thick vertically integrated system. The system consists of a layer of microfabricated silicon channels for temperature management integrated to radiation-tolerant microfabricated 3D sensors, with electrodes penetrating perpendicularly to the silicon bulk, bump-bonded to an ATLAS FE-I4 pixel readout chip of 100 µm thickness, 2 × 2 cm2, and 26,880 pixels (each measuring 250 × 50 μm2). The system’s electrical and temperature characterization under CO2 cooling as well as the response to minimum ionizing particles from radioactive sources and particle beams before and after 2.8 ×1015 neq cm−2 proton irradiation will be discussed.